Segmentation of Organic and Inorganic Food Consumers at Kebonsari Village, Sukun District, Malang City - Herman, Amaliavani Trintan Mardiati; Relawati, Rahayu; Tain, Anas (Jurnal Dinamika Sosial Ekonomi, 2024)
Consumption of organic food is caused by a variety of factors including sustainability concern, health awareness, environmental considerations, and sensory satisfaction. The research carried out in Malang City - East Java, highlighting the underlying drivers of organic food consumption. This research studies a growing landscape of modern consumer segmentation that increasingly emphasizes food safety and health considerations. The aim of this study is to analyze consumer segmentation based on demographics, compare the value of organic and inorganic rice spending, and compare organic and inorganic vegetable spending. The study was conducted at Kebonsari village, Sukun district, Malang city, using primary data obtained from the distribution of questionnaires and interviews with 60 respondents. The sampling method used is multistage sampling. While data are analyzed with paired sample t-test. The results show that consumers with high income and education have a consciousness of the importance of health so have a willingness to consume organic food. The study results show that consumers with high income and education have awareness of the importance of health, so that they have the willingness to consume organic food. The volume and value of organic and inorganic rice purchase differ between education levels and income. Consumers prefer to consume organic rice and organic vegetables. The difference also occurs in the purchasing value of organic and inorganic vegetables. Consumers with higher incomes tend to buy organic vegetables for daily consumption.